Non-Resident Second Amendment Rights after Dearth v. Lynch - Specht, Steven K.; Piccolo, Michael (Revista de Investigações Constitucionais, 2016)
Two federal statutes have unwittingly resulted in depriving nonresident United States citizens of a constitutional right to bear arms. This article considers the background of the statutes, the rights and obligations of US Citizens abroad, and past jurisprudence on the Second Amendment. Through analysis of two types of scrutiny, one can consider how far to take the right to bear arms and determine how the right to bear arms should be treated for those who consciously give up permanent residency and live abroad.